SIFAT-SIFAT KAYU NYATOH (Palaquium obtusifolium Burck.) SEHUBUNGAN DENGAN KEMUNGKINAN PENGGUNAANNYA SEBAGAI BAHAN BILAH PENSIL - Yance I Mandang; Herpin Suhaendra (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Jelutung wood (Dyera spp Apocynaceae) has been the main source of pencil slat in Indonesia for more than 30 years. It can easily be peeled with pencil sharpener specially designed for children usage. However the supply of jelutung wood is no longer sufficient to meet the rising demand for pencil slat. It is therefore necessary to search for substitute.Previous study with jelutung and other wood species indicated that the peelability of wood depend not only on wood density but also on anatomical structure. The occurrence of closely spaced parenchyma lines in jelutung enhances the ease of wood to be peeled. The closely spaced parenchyma lines acted as if they were chopped lines inside the wood tissue that made the wood peelable. So the prospective substitute should have similar parenchyma pattern with jelutung 's.Nyatoh (Palaquium spp. Sapotaceae) is known to have closely spaced parenchyma bands similar to that of jelutung's. The purpose of the present study is to find out whether or not nyatoh wood could be used for pencil slat, as a substitute for jelutung wood in pencil production.Sample of nyatoh wood (Palaquium obtusifolium Burck.) used in this experiment was obtained from Sulawesi. The sample was processed into pencil at PT Staedtler Indonesian factory in Serang, using 28 grade graphite lead. The peelability test were assisted by primary school student class II, llI, and IV, using simple rotary pencil sharpener. Pencils made of jelutung were used as controls. An independent test was used to analyze whether or not nyatoh wood is easy to be peeled, and whether or not the pee/ability depend on the age of the student and on the wood species used. The anatomical structure and the density of the wood sample were also observed.The result of experiment indicated that nyatoh wood with sample density ranges from 0.40 0.57 gr/cm3 was easily peeled with pencil sharpener, either by primary school student class IV, and by class II as well. Further test also indicated that nyatoh had the same peelability with jelutung wood. So it is possible to use nyatoh wood as jelutung substitute in pencil production. Moreover, the colour of nyatoh is already reddish brown so it does not need staining with colour substance as usually being done to jelutung. Key word: Nyatoh, Palaquiurn obtusifoliurn, wood anatomy, peelability, pencil slat.